Penerapan Konsep Internet of Things pada Pengembangan Aplikasi Portal Alumni di Universitas Terbuka - Arif, Erman; Julianti, Eka; Paulina Soko, Imelda (Technomedia Journal, 2023)
The internet of things is one of the pillars of Industry 4.0 so that competence in concepts and practices is very useful. Alumni are an inseparable part of the world of education, but often the existence of alumni is not well organized, so there is still a mismatch of alumni data with the existing reality. Every year, the Open University graduates thousands of students from various study programs. After graduating from college, data and information about Alumni are difficult to obtain and communication between alumni is not going well, because currently UT does not have an alumni portal like some other universities have. so that with this Portal alumni can communicate well and exchange information. Currently UT Alumni only exchange information through social media such as WhatsApp Group, Facebook, etc. And this cannot be controlled by UT. Therefore we need a Portal that is able to be a solution to these problems. This study aims to create an Alumni Portal with the application of the Internet of Things in the form of an online website using the Research and Development (R&D) method. Application development is limited to prototypes because further study is required for implementation.